Associations Between Women's Economic and Social Empowerment and Intimate Partner Violence: Findings From a Microfinance Plus Program in Rural North West Province, South Africa. Issue 15 (August 2021) - Ranganathan, Meghna; Knight, Louise; Abramsky, Tanya; Muvhango, Lufuno; Polzer Ngwato, Tara; Mbobelatsi, Mpho; Ferrari, Giulia; Watts, Charlotte; Stöckl, Heidi
Given the mixed evidence on whether women's economic and social empowerment is beneficial or not for reducing intimate partner violence (IPV), we explored the relationship between women's empowerment and IPV risk. We analyzed data from baseline interviews with married women ( n = 415) from the Intervention with Microfinance and Gender Equity (IMAGE) longitudinal study in rural South Africa. IMAGE combines a poverty-focused microfinance program with a gender-training curriculum. We fitted logistic regression models to explore associations between women's economic situation/empowerment and IPV. For the multivariable logistic regression, we fitted three models that progressively included variables to explore these associations further. Women who reported "few to many times" for not earning enough to cover their business costs faced higher odds of past year physical and/or sexual violence (adjusted odds ratio [aOR] = 6.1, 1.7-22.3, p = .01). Those who received a new loan experienced higher levels of past year emotional (aOR = 2.8, 1.1-7.4, p = .03) and economic abuse (aOR = 6.3, 2.2-18.5, p = .001). Women who reported that partners perceived their household contribution as not important faced higher odds of past year economic abuse (aOR = 2.8, 1.0-7.8, p = .05). Women who reported joint decision-making or partner making sole reproductive decisions reported higher levels of past year physical and/or sexual violence (aOR = 5.7, 0.9-39.4, p = .07) and emotional abuse (aOR = 3.0, 0.9-10.2, p = .08). Economic stress and aspects of women's empowerment, alongside established gender roles within marital relationships is associated with IPV risk in rural South Africa. Although improved economic conditions for women appears to be protective against physical and sexual IPV, associations between certain indicators of women's economic situation, empowerment, and IPV are inconsistent. We need to consider complementary programming and all types of IPV in research, intervention, and policy, as different aspects of empowerment have varying associations with different types of IPV (physical, sexual, emotional, and economic abuse).